2014
DOI: 10.1080/09712119.2014.980417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of piroxicam and ascorbic acid combination on live weight and rectal temperature of savannah brown goats during post-operative pain management

Abstract: Evaluation of the effect of piroxicam and ascorbic acid combination on live weight and rectal temperature of savannah brown goats during post-operative pain management,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Increase in the rectal temperature has been used as an indicator for postsurgical pain (Sanford et al, 2006;Landa 2012) due to the stimulation of autonomic sympathetic system trigger the releases of adrenaline elevates body temperature (Koknaroglu and Akunal, 2013). Okafor et al (2014) reported the decreasing effect of NSAIDs on rectal temperature. They inhibit neurotransmitter that mitigates the release of adrenocorticotropic hormone from the hypothalamic pituitary system (Karanth et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in the rectal temperature has been used as an indicator for postsurgical pain (Sanford et al, 2006;Landa 2012) due to the stimulation of autonomic sympathetic system trigger the releases of adrenaline elevates body temperature (Koknaroglu and Akunal, 2013). Okafor et al (2014) reported the decreasing effect of NSAIDs on rectal temperature. They inhibit neurotransmitter that mitigates the release of adrenocorticotropic hormone from the hypothalamic pituitary system (Karanth et al, 2000).…”
Section: Discussionmentioning
confidence: 99%